Fiscal policy in a growth framework - Norman Gemmell (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper assesses recent theorising and empirical evidence on the impact of fiscal policy—taxes, public expenditures and budget deficits—on long-run growth. It considers the relevance of recent advances in growth theory for low-income countries and compares the evidence for low-income countries with that for middle- and highincome (OECD) countries. Recent advances in endogenous growth theory have demonstrated that fiscal policy can have long-run effects on economic growth rates where some taxes distort investment decisions in the private sector (negative effect) and/or where some `productive' public expenditures compliment private investment (positive effect). Increasing budget deficits can be expected to reduce long-run growth rates, unless tax-payers fully anticipate fiscal policy changes and adjust their savings behaviour accordingly—a condition unlikely to hold in low-income countries. Recent theory particularly stresses the importance for growth of the following. The composition of taxes and expenditures—distortionary versus nondistortionary taxes; productive versus unproductive expenditures. — The government budget constraint (GBC)—growth effects of additional public spending inevitably must be balanced against the growth effects of the taxes or deficits which finance them. — Distinguishing the short- and long-run. Since most growth models agree that fiscal-growth effects occur in the short-run, an important policy question becomes: for how long do fiscal-growth effects persist? There is a great deal of empirical evidence on the effects of fiscal policy on long-run growth. Much of this however is methodologically weak rendering results unreliable. Research prior to around 1997 (and some thereafter) generally ignores the GBC when testing for fiscal effects and as a result produces non-comparable or apparently nonrobust results. More consistent evidence is found (though almost all of this is for the OECD) when the growth effects of taxes, expenditures and deficits are examined simultaneously—as the GBC suggests. Negative effects of taxes which distort investment decisions (e.g. income taxes) and positive effects of `productive' expenditures (e.g. capital spending such as infrastructure; education) are generally found. Taxes on domestic goods and services and government recurrent and/or welfare spending appear generally to have, at most, weak effects on long-run growth. Evidence on the effects of redistribution (of which fiscal policy is a part) on growth is ambiguous, consistent with the ambiguous predictions from current theorising. There is very little reliable evidence available for LICs; limited evidence for LDCs more generally suggests the possibility that fiscal-growth effects could be quite different from those observed in OECD countries. Robust evidence of a negative association between budget deficits and growth is beginning to emerge, though interpretations differ.
Keywords: O23; O40; 330; fiscal policy; public expenditure; taxation; economic growth; Finanzpolitik; Steuer; Öffentliche Ausgaben; Haushaltsdefizit; Wirtschaftswachstum; OECD-Staaten